Sustainable public procurement - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This guidance note aims to assist ADB staff and borrowers (including grant recipients) on how to incorporate aspects of sustainability in the public procurement process.
Introduction - - ADB’s Approach to Sustainable Public Procurement - - Responsibilities - - Sustainable Public Procurement Criterion Standards and Labels - - Sustainable Public Procurement and the Use of Technology and eProcurement - - Sustainable Public Procurement in Other Lending Modalities - - Conclusion.
Keywords: Letting of contracts -- Handbooks, manuals, etc